Speech vs. reading comprehension: an explorative study of gender representations in Norwegian. Issue 7 (3rd October 2017) - Gabriel, Ute; Behne, Dawn M.; Gygax, Pascal M.
ABSTRACT: As research on the construction of a mental representation of referent gender in speech comprehension is scarce, this study examined whether factors identified in reading comprehension exert similar influence in speech comprehension. Conceptually replicating previous research, a sentence continuation evaluation task was set up in two modalities, as a listening task and as a time-confined reading task (i.e. to correspond to the time constraint when listening). In line with previous findings from self-paced reading paradigms we found gender representations in language comprehension to be grounded in the interaction between textual (grammatical) and background (stereotypical) information. Extending previous research, the effect of stereotypical information was however modulated by presentation modality. In all, although speech and reading comprehension share higher-level processes of comprehension, this study provides first evidence that differences in comprehension might occur due to differences such as orthographic access or attention allocation.